2006
DOI: 10.1007/s00066-006-1517-9
|View full text |Cite
|
Sign up to set email alerts
|

Therapy-Associated Late Effects after Irradiation of Malignant Diseases in Childhood and Adolescence. Feasibility Analyses of a Prospective Multicenter Register Study

Abstract: This prospective evaluation of radiotherapy and radiogenic side effects in children and adolescents will allow correlating doses at organs at risk and the incidence of acute and late sequelae in Germany. Further documentations and a longer follow-up are necessary to obtain powerful results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
5

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 11 publications
1
30
0
5
Order By: Relevance
“…Morphological and physiological studies have identified the renal tubule system as the site of maximum radiation damage [3,6,10,11,14,28,[31][32][33]. According to the results of our study, tubular toxicity induced by 6-Gy irradiation was seen over a period of 6 months.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Morphological and physiological studies have identified the renal tubule system as the site of maximum radiation damage [3,6,10,11,14,28,[31][32][33]. According to the results of our study, tubular toxicity induced by 6-Gy irradiation was seen over a period of 6 months.…”
Section: Discussionmentioning
confidence: 71%
“…Kidneys are probably the most radiosensitive abdominal organs; a tolerance dose of 20 Gy has been proposed [18,19,23]. Radiation nephropathy includes increased vascular permeability, perfusion disturbance, inflammatory reactions, and fibrosis [3,7].…”
Section: Introductionmentioning
confidence: 99%
“…After the end of the EF-radiotherapy, simulation and verification films of every individual patient as well as the treatment data were analysed by an expert panel. One important achievement of this retrospective quality control was to show that deviations of radiation treatment portals and radiation doses from prospective treatment prescriptions proved to be unfavourable prognostic factors for patients with early-stage HL (Figure1) [5][6][7][8][9][10].…”
Section: Clinical Results In Early-favourable Stages From a Single Ramentioning
confidence: 99%
“…The structure of "RiSK" as well as detailed information about documentation procedures has recently been published [4,5]. In short, documentation forms including evaluation of treatment period, fractionation schedule, target volume, radiation technique and dose including detailed information about organ dose levels were established.…”
Section: Methodsmentioning
confidence: 99%